ILLOCUTIONARY ACT ANALYSIS OF JOKOWI THREE PERIODS ON CNBC NEWS 2022: CRITICAL DISCOURSE ANALYSIS - Benny Dele Bintang Ananta (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2023)
This paper discusses the highly controversial issue of postponing the 2024elections. The postponement of the election was replaced with the discourseof extending President Joko Widodo's leadership term.The major objective of this study is to categorize various illocutionary actsand provide a concise description of how they are used by speakers in CNBCnews content. In this investigation, the author uses descriptive qualitativeresearch techniques to collect and dissect information from writing with thetitle "Dokumen Indonesia Maju Bocor, Benarkah Jokowi 3 Periode?". Theanalysis of the data revealed that the language employed by speakers in CNBCnews predominantly consists of representative speech acts across three terms.These categories encompass representative, directive, commissive,declarative, and expressive elements within the news discourse. Theresearcher also found that speakers used 40% representative, 20%commissive, 20% expressive, 10% directive, and 10% declarative in the news.In addition, the speakers' speech in the news is explained from the fivecategories that most of the speakers use: representative, commission, andexpressive. However, the three-period issue has a lot of unfavorableimplications for President Jokowi because it can create unwanted chaos in thepolitical environment for those who agree or disagree with the issue.